Effect of IFRS adoption on financial reporting quality of SMEs: a case of Harare CBD - Mandaza, Tatenda (Midlands State University, 2018)
The aim of the research is to analyse the effects of adopting IFRS for SMEs on quality of accounting reports of SMEs in Harare CBD. The targeted population size used in this research was 18 and the sample size was constituted by 11 respondents. The information obtained from the data collected was analysed using the qualitative approach. From the research the research findings also show that adopting IFRS significantly affects the quality of accounting reports of SMEs. In measuring the quality of accounting data presented in the financial statements, SMEs used different method. The use of the conceptual framework and accounting conservatism methods were the most applied by SMEs. The findings also indicated that the legal framework of the country was a major determinant of accounting reporting for SMEs. The SMEs who participated in the study, had mixed feelings on the impact of IFRS on their accounting reports. Benefits and challenges of adopting IFRS were also cited by these SMEs. The researcher discovered that SMEs need assistance from all stakeholders in order to improve awareness of adopting the IFRS. The recommendation was that the government should assist in minimizing the cost of adopting IFRS and business stakeholders to help with the relevant resources required to implement IFRS for SMEs.